Surface structure and bonding in the strongly correlated metal oxides NiO and UO2 - Castell, M; Dudarev, S; Muggelberg, C; Sutton, A; Briggs, G; Goddard, D (1998)
We show atomic resolution elevated temperature scanning tunneling microscope images of the NiO (001) and UO2 (111) surfaces. When imaging the empty states structure of NiO, a fourfold symmetric hole state is observed around defects and step edges which influences the second nearest neighbor Ni ions. A similar effect is not observed on the UO2 (111) surface. We explain this difference in terms of the degree of covalent coupling that is involved in the bonding of these oxides. Modeling of the electronic structure through the local spin density approximation incorporating the Hubbard U is used to create charge density maps which show that there is a significant element of nonsphericity of charge distribution around the Ni ions in NiO, but that the distribution is spherical in UO2. (C) 1998 American Vacuum Society.